Reflexiones sobre las evoluciones recientes de las relaciones Sur-Sur - Herrera, Remy (2024)
Recent steps of regional integration in Latin America are quite important, especially the CELAC. The ALBA. which followed the failure of ALCA. could serve as an inspiration for África and Asia. The BRICS could also mean the beginning of a multipolar world. Economic exchanges between Asia and Africa are interesting, but not necessary equitables. The new dynamic requires an adjustment of the North-South relationships and a new postneoliberal and socialist perspective.